Examining the Contribution of Nurse Practitioners to Geriatric and Palliative Care in Israel - Rachel Nissanholtz-Gannot; Keren Grinberg; Shoshy Goldberg; Hilla Fighel; Yael Sela; Yafit Cohen; Rivka Hazan Hazoref (Nursing Reports)
Background/Objectives: Nurse practitioners (NPs) play a pivotal role in delivering medical care, leveraging their specialized training and broader range of authorities than registered nurses, as approved by the Ministry of Health. Since 2009, Israel has expanded NP training to include diverse specialties such as palliative care, geriatrics, diabetes, surgery, and health policy. Introducing a new professional role into the health system is a complex, resource-intensive process that requires collaboration across stakeholders. Globally, NPs are recognized for preventing hospitalizations and achieving improved care outcomes, with high patient satisfaction. However, in Israel, NPs’ perceptions of their role and contributions remain underexplored. This study aims to assess NPs’ role perception, contributions to the health system, and attitudes toward their professional development in palliative and geriatric care. Methods: The mixed-methods study included 26 in-depth interviews with palliative and geriatric NPs and an online survey of 89 NPs (29 in geriatrics and 60 in palliative care). Results: Most NPs are women (84%), Israeli natives (69%), and Jewish (64%). More than half (53%) have 1–4 years of experience as practitioners, and 71% are employed full time. Regarding their work environment, the NPs feel that their supervisors and patients are appreciative of their work and that they are considered professional authorities. The qualitative findings also point to several challenges in their work: (1) The NPs’ status vis-à-vis medical staff and patients is insufficiently established; (2) the NPs lack practical and theoretical learning over time; (3) there is a shortage of positions; and (4) there is a sense of high work and emotional load and difficulty in implementing palliative care within the health system. With regard to their training, 58% of NPs were satisfied with the course, while 71% felt it lacked content. Looking forward, 76% of the NPs believed that over the next five years, the NP role would expand significantly, and 88% would recommend that other nurses become NPs. Conclusions: To maximize NPs’ potential, the study recommends clarifying their role, expanding authorities, aligning training with professional demands, and fostering trust between NPs and the medical establishment. Branding efforts and emotional support for NPs, especially in palliative care, are essential to enhance their integration and effectiveness in the health system.